Family‐based preventive intervention for children of parents with severe mental illness: A randomized clinical trial - Anne Dorothee Müller; Ida Christine Tholstrup Gjøde; Nikolaj Thams; Sidsel Ingversen; Mala Moszkowicz; Jens Richardt Møllegaard Jepsen; Lisbeth Juhl Mikkelsen; Signe Sofie Nielsen; Nicoline Hemager; Merete Nordentoft; Anne A. E. Thorup (Wiley, 2024)
Abstract Background Children of parents with a severe mental illness have an increased risk of developing a lifetime mental illness. We aimed to compare the effects of a preventive family‐based intervention, VIA Family, with treatment as usual (TAU) on these children's global functioning. Methods Between 2017 and 2021, we conducted a pragmatic, rater‐blinded, two‐arm parallel‐group superiority trial in Denmark. Families with at least one child aged 6-12 years and at least one biological parent with schizophrenia spectrum disorder, bipolar disorder, or recurrent major or moderate depression were included. We randomly allocated 95 families with their 113 children to VIA Family or TAU (ratio 1:1). VIA Family was individually tailored and based on case management. The intervention included options for psychoeducation, parental support, and treatment for emerging child psychiatric symptoms. Blinded raters assessed children and their families at baseline and after 18 months. The primary outcome was the difference in change between groups at end‐of‐treatment in daily global functioning measured with the Children's Global Assessment Scale. Secondary outcomes were emotional and behavioral problems and days absent from school. We analyzed data blinded to allocation. Results At post‐intervention, differences in mean change from baseline between VIA Family and TAU were non‐significant (CGAS: −1.20, 95% CI = −6.61; 4.21, p = 0.66), as were the differences on the secondary and exploratory outcomes. Conclusion Contrary to our hypothesis, we did not find a superior effect of VIA Family compared with TAU. The short follow‐up period and large sample heterogeneity might explain the null findings. Therefore, a possible long‐term, preventive treatment effect has yet to be explored.